2020
DOI: 10.1002/pca.2940
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity and quality evaluation of different Rhodiola species and commercial products based on NMR‐spectroscopy and HPLC

Abstract: Introduction: The main concern regarding the authenticity and quality of Rhodiola rosea L. (Sedum rosea (L.) Scop.) products is their adulteration with other Rhodiola species. Objective: The aim of the study was the development of a reliable and practical analytical platform for quality and quantity assessment of the characteristic molecules in three Rhodiola species (R. rosea, R. kirilowii (Regel) Maxim and R. crenulata (Hook. f. & Thomson) H. Ohba), commercial products and their possible application as marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
(91 reference statements)
0
23
2
Order By: Relevance
“…That has led, unsurprisingly, to frequently reported adulteration, as well as low‐quality and even unsafe products [ 13 ]. As many adulterants are difficult to discriminate, there is an urgent need not only to develop artificial cultivation technologies, but also a consolidated worldwide program for quality assessment of phytomedicine [ 93 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…That has led, unsurprisingly, to frequently reported adulteration, as well as low‐quality and even unsafe products [ 13 ]. As many adulterants are difficult to discriminate, there is an urgent need not only to develop artificial cultivation technologies, but also a consolidated worldwide program for quality assessment of phytomedicine [ 93 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Metabolomics employs different analytical platforms including high-performance liquid chromatography (HPLC) [22][23][24][25][26][27], Fourier transformed infrared (FT-IR) spectroscopy [28][29][30][31], mass spectrometry (MS) [32][33][34][35] and nuclear magnetic resonance (NMR) spectroscopy [36][37][38][39][40][41][42].…”
Section: Metabolomics Analytical Toolsmentioning
confidence: 99%
“…Extracts or pure myconoside from the Orpheus' flower have revealed a remarkable antioxidant and anti-aging activity [12], as well as, cytoprotective [13], radioprotective, anticlastogenic, and stimulatory effect on the regeneration of human fibroblasts in vitro [1,14]. Our previous expertise with phenylethanoid glucosides-rich extracts or pure molecules, such as verbascoside and forsythoside B, provided evidence on their anti-inflammatory activity on interferon gamma (IFN-γ) stimulated primary cultures of normal human keratinocytes [15]. In the last several years, two reports have shown that phenylpropanoids can act as activators of Nrf2 affecting Nrf2-ARE luciferase reports cell activity, Nrf2 protein level, and its downstream target genes expression [16,17].…”
Section: Introductionmentioning
confidence: 99%